Avaliação da logística de distribuição de produtos em uma empresa de e-commerce - Pileggi, Gisele Castro Fontanella; Rosa, Renata de Oliveira (Revista Gestão da Produção Operações e Sistemas, 2007)
All enterprises, either physically or virtually established, face, on a daily basis, problems that involve the allocationof vehicles and the schedule for the sequence of their assistance services. In general, the purpose is to improvethe process efficiency, thus reducing costs and increasing the quality of the services offered. In this context,it is defined the Vehicle Routing Problem (VRP), which consists of assigning routes, starting and finishing theprocess in a warehouse or distribution center, considering all the problems’ restrictions leading it to the least costpossible. In order to solve this problem, heuristic methods are used, due to the difficulty in applying the exactalgorithms to practical problems. A case study was accomplished in a physical and virtual enterprise, locatedin the city of São Paulo, with the purpose of evaluating its distribution process. A mathematical model for theVRP (BODIN et al., 1983) was implemented, by using the LINGO modeling language. The solutions obtainedby the enterprise were compared with the ones obtained by the Clarke and Wright method (1964), and by thesolutions obtained by the LINGO. The results demonstrate the applicability of these methods for minor practicalproblems.Keywords: Logistics; Electronic commerce; Vehicle Routing Problem.